Input and Output of Tuna Fishing Operations Using Longline Vessels Based at Cilacap Ocean Fishing Port - Kyssha Alya Larasati; Vita Rumanti Kurniawati; Yopi Novita (International Journal of Marine Engineering Innovation and Research, 2026)
Tuna fishing not only generates significant economic profit, but also has negative environmental impacts due to the intensive use of materials, equipment, and energy. This study aims to identify and measure the input and output components of the tuna fishing process using longline vessels at the Cilacap Oceanic Fisheries Port through a life cycle inventory (LCI) approach. Data collection was carried out through field observations and structured interviews with 30 selected stakeholders, including the analysis of vessel specifications, fishing gear, and supplies. The results of the study show that supplies dominate operational inputs with a total mass of 62,026 kg/year. This indicates a high resource intensity, requiring 29.31 kg of material  input to produce 1 kg of tuna. In addition, this activity produces outputs in the form of significant environmental impacts, including Sulfur Oxide (SOx) emissions of 707.62 kg/year due to diesel fuel combustion and solid waste of 33,550 kg/year, predominantly consisting of single-use plastic packaging from leftover supplies. These findings indicate the need for improvements in logistics components from the upstream side and waste management strategies in the fisheries sector.